Automated Robotic System for Efficient Solar Panel Dust Removal Using GPS-Based Navigation - Murugaperumal K.; Karuppiah Natarajan; Jain H.S.; Ganesh Burra; Shahitya Banoth; Akshay Gujjala (E3S Web of Conferences)
The dust which is deposited on the top of the solar panels reduces the efficiency of solar panels which leads to decrease in energy output and it also affects the performance of the system. To overcome this problem, this project proposes the removal of the dust on the solar panels with the help of robot without human intervention. Traditional cleaning methods to remove the dust require labor. So dust is removed on the solar panels with the help of robot.This paper describes about the solar panel dust removal using robot which automatically traverse array of solar panels and it also detects the dust and this kind of system efficiently cleans the dust on the solar panels and it also involves many other components which are helpful for the detection of the dust on the solar panels. It utilizes a navigation system based on the GPS which helps in the precise and accurate positioning and resulting in enhancing of the operational efficiency.